2015
DOI: 10.1161/circimaging.114.002676
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Epicardial Fat Volume and Extent of Coronary Artery Calcification, Severity of Coronary Artery Disease, or Presence of Myocardial Perfusion Abnormalities in a Diverse, Symptomatic Patient Population

Abstract: Background Epicardial fat may play a role in the pathogenesis of coronary artery disease (CAD). We explored the relationship of epicardial fat volume (EFV) with the presence and severity of CAD or myocardial perfusion abnormalities in a diverse, symptomatic patient population. Methods and Results Patients (n=380) with known or suspected CAD who underwent 320-detector row CT angiography, nuclear stress perfusion imaging, and clinically driven invasive coronary angiography for the CORE320 international study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 44 publications
7
48
1
2
Order By: Relevance
“…Nevertheless, while we have recently reported that high EAT volume is associated with the presence of NCP on CCTA in patients with a CCS of zero [26], another group has reported that baseline and serial change in EAT volume are not related to the development of incidental coronary artery calcification in a similar population [27]. Furthermore, a recent study in a diverse population of symptomatic patients did not find a significant relationship between EAT volume and the presence and extent of coronary arterial calcification measured by cardiac CT [28].…”
Section: Volumetric Assessment Of Eatmentioning
confidence: 96%
“…Nevertheless, while we have recently reported that high EAT volume is associated with the presence of NCP on CCTA in patients with a CCS of zero [26], another group has reported that baseline and serial change in EAT volume are not related to the development of incidental coronary artery calcification in a similar population [27]. Furthermore, a recent study in a diverse population of symptomatic patients did not find a significant relationship between EAT volume and the presence and extent of coronary arterial calcification measured by cardiac CT [28].…”
Section: Volumetric Assessment Of Eatmentioning
confidence: 96%
“…On a random sample of 100 coronary calcification and atheroma [4]. However, a recent multicenter study reported no association between EAT volume, coronary calcium score, and prevalent CAD [5]. Thus, there is still uncertainty as to whether EAT is a marker of general adiposity or a coronary atherogenic fat depot [6].…”
Section: Body Fat Massmentioning
confidence: 99%
“…12 Recently, data from the CORE320 multicenter study database did not find significant adjusted associations between epicardial fat volume and coronary calcium score, CAD as defined by quantitative coronary angiography, or myocardial perfusion abnormalities by single-photon emission tomography in 380 symptomatic patients with intermediate-high risk features. 13 In addition to the question of adequate adjustments in prior studies, these results draw attention to the role of patient characteristics for the significance of epicardial fat volume as a marker for CAD.…”
mentioning
confidence: 98%